Study of the Potentiality of Using Three Raw Materials from Burkina Faso in Porcelain Formulations - Sawadogo, Youssouf; Zerbo, Lamine; Sawadogo, Moustapha; Seynou, Mohamed; Gomina, Moussa; Blanchart, Philippe (Recent Trends in Chemical and Material Sciences Vol. 7, 2022)
Porcelain is a ceramic product formulate from a typical triaxial mixture: clay and kaolin; quartz; feldspar. The use of three mineral materials from Burkina Faso in the formulation of porcelains has been studied. The characterization results showed that the clay « NONG » contains kaolinite (62%), illite (18%), quartz (17%) and rutile (1%). The pegmatite « PEG » contains albite (17%), muscovite (44%) and quartz (34%). The sand « SAB » is mainly composed of quartz. Formulation of traditional hard porcelain generally requires 50% kaolin, 25% silica and 25% feldspar. Some samples were shaped by casting into porous molds and sintered at temperatures ranging from 1200 °C to 1300°C. During firing, clay « NONG » has a role in mullite recrystallization and the formation of a vitreous phase. « PEG » contributes to the quantity and behavior of the liquid phase at temperatures above 1050 °C. It contributes to taking control of sintering process, allowing a virtually zero (<0.5%) open porosity. « SAB » promotes thermal and dimensional stability thanks to its high melting point and is involved in recrystallization processes and liquid phase behavior. XRD of all specimens shows that it composed amorphous, mullite and quartz phases. Characterization of the specimens sintered at 1250 °C evidenced interesting results: a density ranging from 2.3 to 2.5; a water absorption below 0.5%; an open porosity of less than 1%; a flexural strength above 35 MPa. Consequently, materials fired above this temperature are closely related to the porcelain group.